A discourse analysis on historical biographies in english and vietnamese - Nguyễn,Đoàn Thảo Chi (ĐHĐN., 2015)
This thesis was done in an effort to investigate the discourse features of historical biographies in English and Vietnamese. The three aspects of discourse feature under investigation were discourse structure, linguistics features and cohesive devices. From the description of discourse features of the biographical genre, similarities and differences between English and Vietnamese historical biographies were identified. The main theoretical bases of this thesis included Labov’s model of narrative structure, Transitivity system in Systemic Functional Grammar and Halliday and Hasan’s view on cohesion. A combination of research methods was used for this thesis such as descriptive method, qualitative and quantitative method, and contrastive analysis method. As regards the data corpus, a total of 60 historical biographies in English and Vietnamese were collected from reliable websites and books about biography. The study revealed that among six types of clauses in the Transitivity system, material and relational clauses were used with the highest frequencies in both English and Vietnamese historical biographies. In terms of structure, a historical biography could be divided into three sections: the Introduction, the Storyline and the Conclusion with different elements in each section. With respect to cohesive devices, personal reference, additive conjunction and repetition were the most common types of cohesion in historical biographies of the two languages. The findings of this thesis have served as a foundation for the researcher to put forward some implications for the teaching and learning of biography writing. In addition, this thesis can be used as a reference for teachers, learners or those who are interested in historical biographies and can provide them with a better understanding of this genre in the light of discourse analysis.